Clinical practice guidance for next‐generation sequencing in cancer diagnosis and treatment (Edition 1.0). Issue 9 (5th September 2018) - Sunami, Kuniko; Takahashi, Hideaki; Tsuchihara, Katsuya; Takeda, Masayuki; Suzuki, Tatsuya; Naito, Yoichi; Sakai, Kazuko; Dosaka‐Akita, Hirotoshi; Ishioka, Chikashi; Kodera, Yasuhiro; Muto, Manabu; Wakai, Toshifumi; et al.
Abstract : In Japan, the social (medical) health‐care system is on the way to being developed to advance personalized medicine through the implementation of cancer genomic medicine, known as "cancer clinical sequencing, " which uses a next‐generation sequencer. However, no Japanese guidance for cancer genomic testing exists. Gene panel testing can be carried out to help determine patient treatment, confirm diagnosis, and evaluate prognostic predictions of patients with mainly solid cancers for whom no standard treatment is available. This guidance describes how to utilize gene panel testing according to the type of cancer: childhood cancer, rare cancer, carcinoma of unknown primary, and other cancers. The level of evidence classification for unified use in Japan is also detailed. This guidance establishes the basic principles of the quality control of specimens, requirements of medical institutions, informed consent, handling of data during the postanalysis stage, and treatment options based on the evidence level. In Japan, gene panel testing for cancer treatment and diagnosis is recommended to comply with this guidance. This is a collaborative work of the Japanese Society of Medical Oncology, Japan Society of Clinical Oncology, and the Japanese Cancer Association.